Prognostic and clinicopathological significance of survivin in gynecological cancer - Agapiti H. Chuwa; David H. Mvunta; David H. Mvunta (Frontiers Media S.A., 2024)
Survivin belongs to the inhibitor of apoptosis protein (IAP) family and is encoded by the baculoviral inhibitor of apoptosis repeat-containing, or BIRC5, gene. It is preferentially expressed in cancers with functional complexity in cell signaling cascades such as extracellular signal-regulated kinases (ERK), mitogen-activated protein kinases (MAPK), heat shock protein-90 (HSP90), epidermal growth factor receptor (EGFR), phosphoinositide 3-kinase (PI3K), signal transducer and activator of transcription (STAT), hypoxia-inducible factor-1 alpha (HIF-1α), vascular endothelial growth factor (VEGF), and others. Survivin plays a role in cell division and cell death, properties that have attracted a large body of research to decipher its therapeutic and prognostic significance in cancer. Survivin has tumor-promoting effects in endometrial (EC) and ovarian (OC) cancers, and its upregulation in endometrial cancer has been associated with poor overall survival (OS). While survivin protein is abundantly expressed in OC, it is barely detectable in normal ovarian tissue or benign ovarian tumors. Survivin expression is also a marker for cervical intraepithelial neoplasia (CIN) and high-risk human papillomavirus, and a predictor of viral clearance and prognosis in uterine cervical cancer (UCC). Furthermore, nuclear survivin expression is very low in normal vulvar squamous epithelium and increases to become abundant in vulvar invasive squamous cell carcinoma (ISCC), conferring resistance to apoptosis in vulvar carcinogenesis. In this review, we discuss in detail the impact of survivin signaling on gynecological cancers and provide insight on its therapeutic and diagnostic potential, existing research gaps, and areas for future research.